2018
DOI: 10.1002/ejp.1192
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of efficacy and safety of eslicarbazepine acetate for the treatment of trigeminal neuralgia

Abstract: Eslicarbazepine acetate has shown to be an effective, safe and well-tolerated drug for TN. This is the first study that evaluated the efficacy of this drug on TN in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…This study supports the hypothesis that ESL is an effective, safe and well-tolerated drug for the treatment of TN (Sanchez-Larsen et al, 2018). We would like to add some considerations that may be useful for the use of ESL in clinical practice off label.…”
supporting
confidence: 82%
“…This study supports the hypothesis that ESL is an effective, safe and well-tolerated drug for the treatment of TN (Sanchez-Larsen et al, 2018). We would like to add some considerations that may be useful for the use of ESL in clinical practice off label.…”
supporting
confidence: 82%
“…91 Efficacy and safety of eslicarbazepine in TN patients was first assessed in 2018. 183 The results of this open-label study that included 15 patients suggested that eslicarbazepine is an effective, safe, and well-tolerated treatment for TN. It is noteworthy that around 60% of the patients presented adverse events, mainly lightheadedness, severe dizziness, and hyponatremia and 4 of the 15 patients discontinued treatment for this reason.…”
Section: Additional Pharmacological Perspectivesmentioning
confidence: 86%
“…It is noteworthy that around 60% of the patients presented adverse events, mainly lightheadedness, severe dizziness, and hyponatremia and 4 of the 15 patients discontinued treatment for this reason. 183 Although the adverse events induced by eslicarbazepine are similar to CBZ and OXC, they are considered less frequent. 184,185 Eslicarbazepine is contraindicated in patients with hypersensitivity reactions to CBZ (European Medicines Agency, London, UK), but some studies have suggested that severe skin reactions occur less frequently with eslicarbazepine compared to other anticonvulsants, leading to treatment discontinuation in only 0.1% of the cases.…”
Section: Additional Pharmacological Perspectivesmentioning
confidence: 99%
“…Although TN, a severe facial pain disorder, has been studied for decades, neither medicines nor surgical treatments can reach satisfactory effects 23 . The molecular mechanism of TN remains unclear and needs further investigation.…”
Section: Discussionmentioning
confidence: 99%